2021
DOI: 10.1039/d0ce01275k
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks derived from a semi-rigid anthracene-based ligand and sulfonates: proton conductivity and dye degradation studies

Abstract: The MOFs were constructed by ligand AHP and sulfonate analogues. MOF4 exhibits a high proton conductivity of 1.95 × 10−3 S cm−1 at 95 °C and 98% relative humidity. MOFs 1–5 also serve as photocatalysts for methylene blue degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The degradation of antibiotics did not significantly diminish when AO was added to the reaction, suggesting that h + was not the major active species either. However, the degradation of antibiotics was significantly inhibited by the addition of BQ and TBA, indicating that O 2 ˙ − and ˙OH played a crucial role [ 58 , 59 , 60 , 61 ] in this photocatalytic reaction and confirming that ˙OH was the major active species, as shown in Scheme 2 .…”
Section: Resultsmentioning
confidence: 77%
“…The degradation of antibiotics did not significantly diminish when AO was added to the reaction, suggesting that h + was not the major active species either. However, the degradation of antibiotics was significantly inhibited by the addition of BQ and TBA, indicating that O 2 ˙ − and ˙OH played a crucial role [ 58 , 59 , 60 , 61 ] in this photocatalytic reaction and confirming that ˙OH was the major active species, as shown in Scheme 2 .…”
Section: Resultsmentioning
confidence: 77%
“…Notably, Zn-pzdc-H 3 O + yields a high proton conductivity of 2.42 × 10 −3 S cm −1 at 323 K and ∼97% RH, outperforming those of some previously reported MOFs, covalent-organic frameworks (COFs), hydrogen-bonded organic frameworks (HOFs) and organic cocrystals (Table S6 in ESI†). 68–93…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous studies reporting that the fluorescence of dyes can be quenched by the G-quadruplex structure 43−45 or be bleached by •OH. 46,47 Thus, we speculate that the fluorescence of RhB would be greatly inhibited after it bound with hemin/G-quadruplex and react with •OH generated by H 2 O 2 , but this fluorescence would immediately recover after adding H 2 S owing to the dismantling of the Gquadruplex, and the activity of hemin in the G-quadruplex was inhibited after it reacted with H 2 S. To verify this hypothesis, molecule docking and a series of fluorescent experiments were employed. From the docking study, it showed that hemin and RhB interacted with the G-quadruplex (Figure 5a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%